Role of the puckered anisotropic surface in the surface and adsorption properties of black phosphorus - Lazar, Petr; Otyepková, Eva; Pykal, Martin; Čépe, Klára; Otyepka, Michal (Nanoscale, 2018)
Nanomaterials have a high surface-to-mass ratio and their surface properties significantly affect their features and application potential. Phosphorene, a single layer of black phosphorus (BP), was the first homoatomic two-dimensional material to be prepared after the discovery of graphene. The structure of phosphorene resembles the honeycomb arrangement of graphene, but its layers are buckled and highly anisotropic. We studied how this difference affects the surface properties of BP, namely the free surface energy and adsorption affinity of various organic molecules. Using inverse gas chromatography, we measured the total surface free energy of BP powder to be 90 mJ m-2 and showed that it was dominantly determined by dispersion forces, but, unlike on graphene, with a notable contribution from specific acid-base interactions. We further measured adsorption enthalpies of volatile organic compounds on BP and rationalized them using density functional theory calculations. Polar molecules showed an increased affinity due to a significant contribution of dipole-dipole interactions to the molecule-surface bonding, because the buckled surface of BP causes higher diffusion barriers than those on graphene, hinders molecular in-plane motion and supports mutual orientation of molecular dipoles over longer distances, in contrast to graphene.